An investigation of flaw-size independence of cohesive traction-separation law at the nanoscale: A molecular dynamics study. (15th June 2019) - Nakarmi, Sushan; Sohail, Tanvir; Roy, Samit
Graphical abstract: Highlights: The traction separation law (TSL) at the nanoscale is a material property independent of flaw size only if stresses near the crack tip are employed. The use of far-field data to define TSL makes the TSL flaw-size dependent. Hence, it is no longer a material property and therefore inaccurate. Abstract: The objective of this paper is to investigate and evaluate, through the application of molecular dynamics (MD) simulations, the validity of obtaining cohesive traction-separation law at the nanoscale using three different approaches: (1) stress data from near the crack tip, (2) stress data from the far-field, and (3) changes in potential energy of the structure due to applied loads. The motivation for this research comes from the fact that the traction-separation law, which is a material property, can exhibit significant dependence on flaw size at the nanoscale if the correct methodology is not employed. The objective of this paper is to mathematically demonstrate that (a) the traction separation law at the nanoscale is a material property independent of flaw size only if stresses near the crack tip are employed to obtain the traction-separation law, and (b) the use of far-field data to define traction-separation law and fracture toughness makes the traction-separation law flaw-size dependent, and hence, it is no longer a material property and therefore inaccurate. Results for a single graphene sheet with and without a center crack under pure Mode I loading are presented to validate these concepts. Future work will focus on verifying these concepts under mixed-mode conditions.